Can the Arts Cure Pandemic Hearts? - Cultural Activity During the COVID-19 Pandemic and its Consequences for Psychological Well-Being. (January 2023) - Gotthardt, Karina Aylin; Rakoczy, Katrin; Tallon, Miles; Seitz, Matthias; Frick, Ulrich
Cultural activities might serve as a buffer to the negative effects of the COVID-19 pandemic on mental health. Frequencies of participants' cultural activities in terms of participation in digital cultural offerings or self-initiated cultural activities during the pandemic are examined, and whether prior cultural engagement and valuing of culture have an impact on this participation. It is explored whether both forms of cultural activities are directly connected with psychological well-being, namely, optimism concerning COVID-19, and whether this relationship is mediated by autonomy, relatedness and aesthetic experience. Regression and mediation analysis were calculated (N = 398). Both cultural activities were related to increased aesthetic experience and perceived autonomy, but only participation in digital cultural offerings was connected to increased perceived relatedness. Relatedness, in turn, was connected to increased optimism. The results reflect the protective function of cultural activities on psychological well-being, demonstrating the importance of cultural life in times of adversity.